PROBLEMS OF THE LAND MARKET FORMATION AND THE ASSESSMENT OF NATURAL RESOURCES - V. Nemchenko; H. Nemchenko (Ekonomìka Harčovoï Promislovostì, 2018)
The issues of formation of the land market and the role of the state in its regulation have been studied in the article. The great importance of the agrarian business (APC)’s reforming is placed on the land market. Its formation was carried out in all countries with economies in transition (CEIT). The necessity of a moratorium on land purchase and sale in present-day conditions in Ukraine has been proved. For Ukraine, the topicality of the solution of this problem lies in the fact that the country, on the one hand, has huge potential in food production, and, on the other hand, the theoretical and practical measures on the formation of the land market and the economic assessment of natural resources have not been fully developed yet. The aim of the research is to come to know the special aspects of the formation of the land market and factors that stop its development, and the development of a concept for the assessment of natural resources, including land ones. The concept of economic evaluation of natural resources, including land, has been developed. The authors believe that the assessment of natural resources should be determined by the cost of their reproduction. The faster the exhaustion of natural resources will occur, the more intense there should be changes in the structure of the country's economy.